2020
DOI: 10.1523/jneurosci.2410-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces Maladaptive Behaviors by Activating Corticotropin-Releasing Hormone Signaling in the Mouse Oval Bed Nucleus of the Stria Terminalis

Abstract: The bed nucleus of the stria terminalis (BNST) is a forebrain region highly responsive to stress that expresses corticotropin-releasing hormone (CRH) and is implicated in mood disorders, such as anxiety. However, the exact mechanism by which chronic stress induces CRH-mediated dysfunction in BNST and maladaptive behaviors remains unclear. Here, we first confirmed that selective acute optogenetic activation of the oval nucleus BNST (ovBNST) increases maladaptive avoidance behaviors in male mice. Next, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 110 publications
5
74
0
Order By: Relevance
“…One possible cause could be a disrupted BNST neuronal circuitry. We and others found that acute optogenetic stimulation of the adult ovBNST increases maladaptive avoidance behaviors 20,21 . The BNST is an important node in the limbic forebrain stress-response circuitry that transmits stress information from structures such as the amygdala and hippocampus to the PVN and thereby participates in regulation of HPA axis responsivity 16 .…”
Section: Els Results In Hyperexcitation Of Ovbnst Crh Neuronsmentioning
confidence: 60%
See 4 more Smart Citations
“…One possible cause could be a disrupted BNST neuronal circuitry. We and others found that acute optogenetic stimulation of the adult ovBNST increases maladaptive avoidance behaviors 20,21 . The BNST is an important node in the limbic forebrain stress-response circuitry that transmits stress information from structures such as the amygdala and hippocampus to the PVN and thereby participates in regulation of HPA axis responsivity 16 .…”
Section: Els Results In Hyperexcitation Of Ovbnst Crh Neuronsmentioning
confidence: 60%
“…BNST CRH neurons, likely through indirect innervation of hypothalamic PVN neurons 16 , are also thought to modulate stress responses [17][18][19] . We and others have reported that optogenetic stimulation of the ovBNST is sufficient to induce avoidance behaviors 20,21 . We also found that ovBNST CRH dysfunction mediates chronic stressinduced avoidance behaviors in adult mice 21 .…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations